Infiltrating monocytes drive cardiac dysfunction in a cardiomyocyte-restricted mouse model of SARS-CoV-2 infection - Dmytrenko, Oleksandr; Das, Shibali; Kovacs, Attila; Cicka, Markus; Liu, Meizi; Scheaffer, Suzanne M.; Bredemeyer, Andrea; Mack, Matthias; Diamond, Michael S.; Lavine, Kory J. (Journal of virology, 2024)
Heart involvement after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection occurs in multiple ways and is associated with worse outcomes in coronavirus disease 2019 (COVID-19) patients. It remains unclear if cardiac disease is driven by primary infection of the heart or immune response to the virus. SARS-CoV-2 is capable of entering contractile cells of the heart in a culture dish. However, it remains unclear how such infection affects the function of the heart in the body. Here, we designed a mouse in which only heart muscle cells can be infected with a SARS-CoV-2 strain to study cardiac infection in isolation from other organ systems. In our model, infected mice show viral infection, worse function, and accumulation of immune cells in the heart. A subset of immune cells facilitates such worsening heart function. As this model shows features similar to those observed in patients, it may be useful for understanding the heart disease that occurs as a part of COVID-19.